2022
DOI: 10.1108/cg-11-2021-0396
|View full text |Cite
|
Sign up to set email alerts
|

Does board chairperson experience matter? Examining the relationship between board attributes and human rights reporting in Kenya

Abstract: Purpose Using the resource dependence and legitimacy theories, this research aims to examine the relationship between board attributes and human rights reporting, as well as the interaction effect of board chairperson experience on the relationship among listed firms at the Nairobi Securities Exchange (NSE). Design/methodology/approach This study collected data from annual reports of firms listed on the NSE from 2009 to 2019 using content analysis to examine how boards influence human rights reporting. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 147 publications
0
0
0
Order By: Relevance
“…The board of directors, particularly the board chairperson, serves as one of the mechanisms to minimize agency conflicts' costs. Recent studies have found that certain characteristics of chairpersons, such as independence (Al-Absy, 2020), experience, age and gender (Amran et al, 2014;Tarus et al, 2023;Azzam and Alhababsah, 2022), have an impact on company outcomes, such as reporting, philanthropy, performance and research and development (R&D) investment, when adopting an agency perspective. From an agency theory perspective, the religiosity level of the chairperson's hometown may enhance their monitoring power and serve as a useful tool to control and monitor agency costs.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The board of directors, particularly the board chairperson, serves as one of the mechanisms to minimize agency conflicts' costs. Recent studies have found that certain characteristics of chairpersons, such as independence (Al-Absy, 2020), experience, age and gender (Amran et al, 2014;Tarus et al, 2023;Azzam and Alhababsah, 2022), have an impact on company outcomes, such as reporting, philanthropy, performance and research and development (R&D) investment, when adopting an agency perspective. From an agency theory perspective, the religiosity level of the chairperson's hometown may enhance their monitoring power and serve as a useful tool to control and monitor agency costs.…”
Section: Hypothesis Developmentmentioning
confidence: 99%